2020
DOI: 10.3390/genes11040351
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle-Mediated siRNA Delivery, Protein Delivery, and CFTR Complementation in Well-Differentiated Human Airway Epithelial Cells

Abstract: Extracellular vesicles (EVs) are a class of naturally occurring secreted cellular bodies that are involved in long distance cell-to-cell communication. Proteins, lipids, mRNA, and miRNA can be packaged into these vesicles and released from the cell. This information is then delivered to target cells. Since EVs are naturally adapted molecular messengers, they have emerged as an innovative, inexpensive, and robust method to deliver therapeutic cargo in vitro and in vivo. Well-differentiated primary cultures of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…To determine if the observed increased CFTR protein expression was functionally relevant, we measured CFTR membrane activity using a halide assay which evaluates the increase of ion transport within cells expressing iodide‐sensitive yellow fluorescent protein (YFP) (Singh et al., 2020), by using forskolin stimulation of CFTR and replacing chloride ions with iodide in cells expressing mutated YFP (Figure 3C). To assess if CFZF‐VPR containing exosomes functionally corrected the CFTR anion channel defect in vitro we evaluated the changes in YFP fluorescence in HuBECs pre‐incubated with CFTR activator forskolin, treated with MSC‐CFZF‐VPR or controls in the presence of the potentiator (VX770) and the corrector (VX809) (Janas et al., 2015, Janas et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if the observed increased CFTR protein expression was functionally relevant, we measured CFTR membrane activity using a halide assay which evaluates the increase of ion transport within cells expressing iodide‐sensitive yellow fluorescent protein (YFP) (Singh et al., 2020), by using forskolin stimulation of CFTR and replacing chloride ions with iodide in cells expressing mutated YFP (Figure 3C). To assess if CFZF‐VPR containing exosomes functionally corrected the CFTR anion channel defect in vitro we evaluated the changes in YFP fluorescence in HuBECs pre‐incubated with CFTR activator forskolin, treated with MSC‐CFZF‐VPR or controls in the presence of the potentiator (VX770) and the corrector (VX809) (Janas et al., 2015, Janas et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated the exosome mediated delivery of modified antisense oligonucleotides into nasal epithelial cells with the F508del mutation, which corrected the CFTR function (Villamizar et al., 2019). Other groups have also demonstrated exosome delivery of siRNA and microvesicle‐mediated delivery of CFTR protein into differentiated human airway epithelial cells providing a powerful genetic tool to functionally correct the Cl‐ channel defect in vitro (Singh et al., 2020). Notably, MSC derived exosomes have been used as a treatment for diseases and disorders of many systems such as the cardiovascular, neurological, musculoskeletal and immune system (Phan et al., 2018), suggesting that they are clinically safe and efficacious.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al showed that human airway epithelial cells were susceptible to delivery of siRNA with EVs derived from A549 cells. [ 225 ] A knockdown efficiency of ≈50% could be achieved for a chosen model gene (hypoxanthine phosphoribosyltransferase). Although a direct comparison with liposome‐based strategies was not made, this cell type is known to be difficult to transfect with standard techniques.…”
Section: Comparison Of Liposomes and Extracellular Vesicles For Drug ...mentioning
confidence: 99%
“…In both models, CFTR channel function was shown to be corrected in exosome-recipient cells. Exosomes have similarly shown utility in delivering small interfering RNA in well-differentiated human AECs ( Singh et al, 2020 ), suggesting value beyond gene transfer for the delivery of gene editing materials. These studies demonstrated the potential application of exosomes as vectors for CFTR transfer and functional correction of the genetic defect in human CF cells.…”
Section: Therapeutic Delivery Vectorsmentioning
confidence: 99%